Lipopolysaccharide Binding Protein and sCD14 are Not Produced as Acute Phase Proteins in Cardiac Surgery - Manuela Kudlova; Pavel Kunes; Martina Kolackova; Vladimir Lonsky; Jiri Mandak; Ctirad Andrys; Karolina Jankovicova; Jan Krejsek (Mediators of Inflammation)
Objectives. The changes in the serum levels of lipopolysaccharide binding protein (LBP) and sCD14 during cardiac surgery were followed in this study. Design. Thirty-four patients, 17 in each group, were randomly assigned to coronary artery bypass grafting surgery performed either with (“on-pump”) or without (“off-pump”) cardiopulmonary bypass. LBP and sCD14 were evaluated by ELISA. Results. The serum levels of LBP were gradually increased from the 1st postoperative day and reached their maximum on the 3rd postoperative day in both “on-pump” and “off-pump” patients (30.33±9.96μg/mL; 37.99±16.58μg/mL), respectively. There were no significant differences between “on-pump” and “off-pump” patients regarding LBP. The significantly increased levels of sCD14 from the 1st up to the 7th postoperative day in both “on-pump” and “off-pump” patients were found with no significant differences between these groups. No correlations between LBP and sCD14 and IL-6, CRP and long pentraxin PTX3 levels were found. Conclusions. The levels of LBP and sCD14 are elevated in cardiac surgical patients being similar in both groups. These molecules are not produced as acute phase proteins in these patients.